1999
DOI: 10.1136/gut.44.3.382
|View full text |Cite
|
Sign up to set email alerts
|

Biased JH usage in plasma cell immunoglobulin gene sequences from colonic mucosa in ulcerative colitis but not in Crohn’s disease

Abstract: Conclusions-There is a fundamental difference in the immunoglobulin genes from patients with ulcerative colitis. Whether this is caused by a diVerence in content of immunoglobulin gene segments in the germline or a diVerence in the recombination mechanism is not known. (Gut 1999;44:382-386)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Splenic Ig H genes sequenced in this study have the same characteristics as Ig H genes previously reported in other peripheral sites (13,16,21,24,25). It is also interesting to note that in this group of 32 splenic Ig genes there are two that use J H 1 segments, whereas no sequences from duodenum, salivary gland, or over 200 previously reported Ig genes from lamina propria plasma cells (10,11,17,19) were found that used J H 1. Because J H 1 is so rarely used anyway, a much larger sampling from spleen than this one would be required to determine whether this is significant.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Splenic Ig H genes sequenced in this study have the same characteristics as Ig H genes previously reported in other peripheral sites (13,16,21,24,25). It is also interesting to note that in this group of 32 splenic Ig genes there are two that use J H 1 segments, whereas no sequences from duodenum, salivary gland, or over 200 previously reported Ig genes from lamina propria plasma cells (10,11,17,19) were found that used J H 1. Because J H 1 is so rarely used anyway, a much larger sampling from spleen than this one would be required to determine whether this is significant.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have indicated that the number of mutations in Ig H genes of gastrointestinal plasma cells is high (10,11,17,19) compared with published reports of the level of mutation in spleen, tonsil, and peripheral blood (16, 20 -25). However, we have shown that the number of mutations in IgA genes in lamina propria plasma cells of the duodenum is higher than the number in IgM genes (17).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…20 This finding is consistent with studies on B-cell receptor gene usage that have demonstrated that infiltrating lymphocytes in UC mucosa are of peripheral rather than mucosal origin. 21,22 IgG1 and IgG4 antibodies predominate in UC, whereas IgG2 antibodies are increased in CD. 23 The prevalence of the IgG1 type has recently been explored and shown to be specific to UC and lead to greater opsonization of mucosal bacteria and a feed-forward maintenance of the polymorphonuclear leukocyte respiratory burst in UC.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the nine patients were women and the group had an mean age of 59 years (range 49-90). Mean duration of disease was 8.4 years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Biopsies were taken from the anterior rectal wall, 5-10 cm from the anal verge.…”
Section: Patients and Controlsmentioning
confidence: 99%